(untitled) (World Economics and Finance Bulletin, 2023)
In this article, housing construction, management of housing construction, improvement of management efficiency, modern management system in the housing fund, housing and communal management, location of housing in the city of Tashkent, housing funds located in the city of Tashkent and monitoring of their technical conditions are explained